2013
DOI: 10.1186/2162-3619-2-17
|View full text |Cite
|
Sign up to set email alerts
|

CD133: a stem cell biomarker and beyond

Abstract: Cancer stem cells (CSCs) or tumor initiating cells (TICs) contribute to tumorigenesis, metastasis, recurrence and chemoresistance. CD133, a pentaspan membrane glycoprotein, has been used as a stem cell biomarker for isolation of stem-like cells from a variety of normal and pathological tissues as well as cell lines since its discovery in 1999. Recent studies are focusing on the functionality of CD133. In this review, we summarize new insights into CD133 regulation and the involvement of CD133 in cell self-rene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
204
1
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 100 publications
7
204
1
11
Order By: Relevance
“…Our study of this human glioma cell line confirms the accumulation or preferential selection of CD133 + cells, a putative brain tumour stem cell marker [15], under prolonged stem cell culture conditions compared to propagation in serum-containing media. Recent studies addressing the effect of different culture conditions in in vitro mouse models of GBM described the robust enhancement of stem cell marker expression and self-renewal capacity of cells transferred from adherent growth to spheroid culture [1].…”
Section: Discussionsupporting
confidence: 52%
“…Our study of this human glioma cell line confirms the accumulation or preferential selection of CD133 + cells, a putative brain tumour stem cell marker [15], under prolonged stem cell culture conditions compared to propagation in serum-containing media. Recent studies addressing the effect of different culture conditions in in vitro mouse models of GBM described the robust enhancement of stem cell marker expression and self-renewal capacity of cells transferred from adherent growth to spheroid culture [1].…”
Section: Discussionsupporting
confidence: 52%
“…The results of this preliminary study was also supported by several other studies that showed a significant increase (p=0.002) of CD133 in lichen planus lesions that turn into squamous cell carcinoma. 28 The existence of a variety of gene expression and chemical mediators/cytokines in premalignant lesions have been studied and proved a meaningful relationship. The discovery of chronic inflammatory cells in all premalignant lesions is assumed to contribute significantly to changes in these lesions into oral cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of CD133 is dynamic and responds to changes in the cell microenvironment. CD133 is involved in diverse cellular processes, including the uptake of glucose and transferrin, autophagy, membrane-membrane interaction, and matrix metalloproteinase functions (21). The expression of CD133 on the cell surface was shown to be a specific marker for CSCs in a number of malignancies, including lung cancer (6,22).…”
Section: Discussionmentioning
confidence: 99%